Patience and Action Pays : A Comparative Analysis of WSS Reforms in Three East African Cities - Mugisha, S.; Brown, A. (2012)
There have been significant efforts in the last 15 years to improve performance in water supply and sewerage services (WSS) operations of most cities in Africa. This has called for a number of reforms. WSS utilities in the three East African capital cities have been among the list that has undertaken such reform. Consequently, a number of legislative, institutional and managerial reforms, all aimed at creating good enabling environments to drive performance, have been undertaken. This paper outlines some of these reforms in WSS operations of the three capital cities of Kampala, Nairobi and Dar es Salaam. We present, amongst other things, the key reform drivers, reforms undertaken, achievements and underlying success factors. We conclude that there is need to synergise the use of incentives, strong leadership, managerial autonomy and accountability as important buttresses for successful reforms. In doing all this, political support and, indeed, support from other stakeholders is important. We also note that reforms need time, adequate stakeholder mapping and incorporation of significant local capacity development to be fully effective.